2004
DOI: 10.1007/s10194-004-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent analgesics consumption in migraineurs: comparison between chronic and episodic migraineurs

Abstract: To assess the frequent consumption of symptomatic medications in migraineurs, we consecutively recruited 536 migraineurs from a headache clinic. Among them, 194 (36.2%) had chronic migraine and 342 had episodic migraine. When grouped according to duration of headache, the proportion of patients with chronic migraine increased from 25.5% to 50.9% as headache history increased from <1 to >20 years. The percentage of patients with frequent analgesics consumption also increased with the duration of headache, in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…Pyrazinamide with its bacteriostatic and bacteriocidal activities, acting as an efficient antitubercular agent [37], was also recognized as an important medication. Also salicylamide and ethenzamide are known as analgesic and antipyretic drugs [38]. They are used as non-prescription painkillers belonging to nonsteroidal anti-inflammatory agents with medicinal uses similar to those of aspirin.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazinamide with its bacteriostatic and bacteriocidal activities, acting as an efficient antitubercular agent [37], was also recognized as an important medication. Also salicylamide and ethenzamide are known as analgesic and antipyretic drugs [38]. They are used as non-prescription painkillers belonging to nonsteroidal anti-inflammatory agents with medicinal uses similar to those of aspirin.…”
Section: Introductionmentioning
confidence: 99%
“…27 In Asian studies, the median CM frequency was 52% (mean 46%), with reported values ranging from 4.7% 27 to 82%. [30][31][32][33][34] A USA study showed that the estimated prevalence of CM in the 50-59 years age group was 1.33% range (0.98-1.81) for women and 0.59% range (0.35-1.00) for men. A systematic review showed that just four studies determined the frequency of CM as a proportion of total migraine (19-41%), as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that just four studies determined the frequency of CM as a proportion of total migraine (19-41%), as in the present study. [30][31][32][33][34] A USA study showed that the estimated prevalence of CM in the 50-59 years age group was 1.33% range (0.98-1.81) for women and 0.59% range (0.35-1.00) for men. 4 Over the age of 60 years, these proportions were 0.56% (0.41-0.76) and 0.26% (0.15-0.44), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the RESS process was adopted for microparticle production of ethenzamide. Ethenzamide is a commonly used non-steroidal anti-inflammatory drug (NSAID), which is used as an analgesic and antipyretic agent for pain relief [15,16]. According to the PubChem database, ethenzamide is a poorly water-soluble drug, and its water solubility is less than 1 mg/mL at 289 K. The poor aqueous solubility of ethenzamide results in poor dissolution, poor absorption, and low bioavailability, and makes drug formulation more difficult.…”
Section: Introductionmentioning
confidence: 99%